1992
DOI: 10.1159/000182293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the GABA<sub>A</sub> Agonist Muscimol on Prolactin Secretion from Human Prolactin-Secreting Adenomas and GH<sub>3</sub> Rat Pituitary Tumour Cells

Abstract: The effect of muscimol, a specific potent GABAA receptor agonist, on prolactin release from human prolactin-secreting tissue was investigated using a perifusion system. Perifusion studies on normal rat anterior pituitary tissue, which has identical GABA receptors to those found in normal human pituitary glands, show that muscimol has a specific biphasic effect on prolactin release. This is characterized by an initial transient stimulation (222.3 ± 21.6% of basal) lasting for 5-10 min followed by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Moreover, the amplitude of the GABA-induced current recorded from GH 3 cells is several orders of magnitude lower than the current measured in pituitary lactotrophs, indicating that GABA A subunit expression is reduced in these cells. This difference is consistent with the lack of an effect of muscimol on PRL release in GH 3 cells (Jones et al, 1992).…”
Section: Functional Roles Of Neurotransmitter Receptors In Anteriosupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the amplitude of the GABA-induced current recorded from GH 3 cells is several orders of magnitude lower than the current measured in pituitary lactotrophs, indicating that GABA A subunit expression is reduced in these cells. This difference is consistent with the lack of an effect of muscimol on PRL release in GH 3 cells (Jones et al, 1992).…”
Section: Functional Roles Of Neurotransmitter Receptors In Anteriosupporting
confidence: 88%
“…Muscimol has been shown to exert a biphasic effect on PRL secretion in perfusion studies using the normal rat anterior pituitary gland, as a transient stimulation lasting for 5–10 min was followed by a more prolonged inhibitory phase. However, muscimol has no effect on basal or TRH-stimulated PRL secretion from GH 3 cells (Jones et al, 1992).…”
Section: Functional Roles Of Neurotransmitter Receptors In Anteriomentioning
confidence: 99%
“…We also investigated seven cell lines derived from the periphery. The pituitary contains functional GABA, receptors, which appear to be involved in the regulation of hormone secretion (Jones et al, 1992;Valerio et al, 1992;Vincens et al, 1992). We therefore investigated the AtT-20 cell line, which secrets ACTH, and was derived from a mouse pituitary tumor (Buonassisi et al, 1962).…”
mentioning
confidence: 99%
“…One effect was stimulatory and exerted through inhibition of tuberoinfundibular dopaminergic neurons [9][10][11]; the other was inhibitory and mediated by GABA receptors present on the membrane of the lactotroph cells [12][13][14], This latter inhibitory regulation of hormonal secretion of PRL cells was accompanied by an inhibition of PRL bio synthesis [15]. However, more recent studies using fast perifusion techniques have not only shown an inhibitory but a biphasic effect of GABA on rat PRL secretion in vitro [16,17], GABA first induces a short-lived stimula tion of PRL basal secretion, which is followed by sus tained inhibition. In this case, the two components of GABAergic control are fully mimicked by muscimol, sug gesting involvement of GABAa receptors alone.…”
mentioning
confidence: 99%
“…Whether GABAergic stimulation is a property specific to the normal pituitary cell remains to be clarified, since it was observed neither in the tumoral cell line GHj-B^ [47] nor in PRL-secreting adenomas [17] in vitro.…”
mentioning
confidence: 99%